The Effectiveness of Training Package based on Executive Functions of Delis-Kaplan on Reading skill of Dyslexic students - Ehtesabi, Akram; Faramarzi, Salar; Ehteshamzadeh, Parvin; Bakhtiarpour, Saeed; Ghamarani, Amir (Journal of Adolescent and Youth Psychological Studies (JAYPS), 2022)
Background and Aim: Reading is considered as one of the first ways to acquire knowledge, and students with poor reading skills learn more during and after school. The present research aimed to evaluate effectiveness of training package based on executive functions of Delis-Kaplan on reading skill of dyslexic students. Method: This was quasi-experimental study with pre and post tests and following up. Statistical population was all male and female students in third grade in Tehran who were studying in 2018-19. Thirty dyslexic students were selected by multi- clustering random sampling, then according to inclusion and exclusion criteria, 15 subjects were selected for experimental group and 15 for control group. Experiment group received training package based on executive functions of Delis-Kaplan in 17 sessions each lasting for 60 minutes, but control group did not. The tools used in present research were Raven intelligence test and reading test of Kormi Noori and Moradi (2018). Data were analysed using covariance analysis by SPSS.22. Results: The results showed that training package based on executive functions of Delis-Kaplan has significant effect on reading skill in dyslexic children (p